1997
DOI: 10.1038/sj.ijo.0800375
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma insulin concentration in regulating glucose and lipid metabolism in lean and obese Zucker rats

Abstract: OBJECTIVE: To determine the role of plasma insulin concentration in regulating glucose and lipid metabolism in insulin-resistant obese Zucker rats and to compare obese rats with lean controls with respect to changes in insulin sensitivity. DESIGN: Animal study of lean and obese rats with or without insulin sensitizer, YM268. ANIMALS: Nine week old male lean (Fa/±) and obese (fa/fa) Zucker rats. MEASUREMENTS: Plasma glucose, insulin, triglyceride (TG), non-esteri®ed fatty acid (NEFA), cholesterol at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…In contrast to the marked hypoglycaemic action of YM268 in obese Zucker rats, YM268 like other insulin sensitizers did not cause hypoglycaemia in lean Zucker rats (35). However, immunoblot analyses in this study revealed that the GLUT4 content of adipose tissue in lean Zucker rats was much higher than in obese rats after YM268 treatment.…”
Section: Pm-glut4 Ratio (%)contrasting
confidence: 85%
“…In contrast to the marked hypoglycaemic action of YM268 in obese Zucker rats, YM268 like other insulin sensitizers did not cause hypoglycaemia in lean Zucker rats (35). However, immunoblot analyses in this study revealed that the GLUT4 content of adipose tissue in lean Zucker rats was much higher than in obese rats after YM268 treatment.…”
Section: Pm-glut4 Ratio (%)contrasting
confidence: 85%
“…Free fatty acids are released into the circulation, in response to this negative energy balance, may reduce peripheral tissue insulin sensitivity (Van Epps‐Fung et al., 1997; Pires et al., 2007). The adverse effect of elevated NEFA concentration on peripheral tissue insulin sensitivity has been observed to be more pronounced in obese rats than in normal rats (Noshiro et al., 1997), as well as in p.p. cows that were overfed prepartum and calved overconditioned [body condition score (BCS)>4] compared with thinner cows (Holtenius et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hormones such as insulin, glucagon, and dexamethasone play a critical role in the liver during glucose homeostasis with a very high sensitivity at a low concentration (pM–nM level) in vivo (Allan and Titheradge, 1984; Noshiro et al, 1997). Although hepatocyte monolayer has been utilized for studying the hormonal response in vitro (Hermsdorf et al, 1999), the effects of hormone on glucose metabolism were not consistent with in vivo and even contradictory with varying incubation conditions (time, medium ingredient etc.)…”
Section: Discussionmentioning
confidence: 99%